Implementing and Internalizing Wasathiyah Islamic Values in a Post-Radicalization Context: The Case of Al-Hidayah Integrated Islamic Boarding School, Aceh Tamiang - Idani, Fitri; Wildan, Raina; Hakim, Lukman (Program Studi Aqidah dan Filsafat Islam, 2025)
Islamic boarding schools are instrumental in promoting moderate Islamic teachings and cultivating values of tolerance and peace, serving as critical bulwarks against the spread of radical ideology. The Al-Hidayah Integrated Islamic Boarding School in Aceh Tamiang represents a unique post-radicalization context, having previously faced allegations of disseminating anti-nationalist ideology. This study examines the implementation and internalization of wasathiyah (moderate) Islamic values at Al-Hidayah after its rehabilitation, with a particular focus on the strategies employed and the challenges encountered. Utilizing a qualitative field research design, data were collected through observation, in-depth interviews with school leaders, teachers, and students, and analysis of institutional documents. The findings demonstrate that wasathiyah values—including moderation, balance, tolerance, consultation, reform, innovation, and nationalism—are systematically integrated into daily activities, the curriculum, extracurricular programs, and public religious study sessions. Teachers function as both primary agents and role models in this internalization process, supported by the use of classical Islamic texts and government-issued materials. However, efforts to entrench wasathiyah values face significant obstacles, notably the diverse backgrounds and perspectives of students, uneven teacher capacity, and diminished government support following the school’s official rehabilitation. This study offers new empirical insight into the complexities of ideological transformation within Islamic educational institutions previously associated with radicalism, highlighting both the progress made and the persistent challenges in sustaining wasathiyah as a foundational ethos.